Signal intensity alteration in the infrapatellar fat pad at baseline for the prediction of knee symptoms and structure in older adults: a cohort study. Issue 10 (26th November 2015) - Han, Weiyu; Aitken, Dawn; Zhu, Zhaohua; Halliday, Andrew; Wang, Xia; Antony, Benny; Cicuttini, Flavia; Jones, Graeme; Ding, Changhai
Abstract : Objective: To describe the associations between infrapatellar fat pad (IPFP) signal intensity alteration at baseline and knee symptoms and structural changes in older adults. Methods: A total of 874 subjects (mean 62.1 years, 50.1% female) selected randomly from local community were studied at baseline and 770 were followed up (only 357 had MRI at follow-up) over 2.6 years. T1-weighted or T2-weighted fat suppressed MRI was used to assess IPFP signal intensity alteration (0–3), cartilage volume, cartilage defects and bone marrow lesions (BMLs) at baseline and 2.6 years later. Knee pain was assessed by self-administered Western Ontario and McMaster Osteoarthritis Index questionnaire. Radiographic osteoarthritis (OA) was assessed. Results: In cross-sectional analyses, IPFP signal intensity alteration was significantly and positively associated with total knee pain as well as knee cartilage defects, BMLs and knee radiographic OA and negatively associated with patellar cartilage volume after adjustment for age, sex, body mass index and/or radiographic OA. Longitudinally, baseline signal intensity alteration within IPFP was significantly and positively associated with increases in knee pain when going upstairs/downstairs as well as increases in tibiofemoral cartilage defects and BMLs, and negatively associated with change in lateral tibial cartilage volume in multivariable analyses. Conclusions: IPFP signal intensity alteration at baseline was associated with knee structural abnormalities and clinical symptoms cross-sectionally and longitudinally in older adults, suggesting that it may serve as an important imaging biomarker in knee OA.